Features of data processing and storage using the virtual file system - Popereshnyak, S.V.; Panchenko, S.V.; Fedorchenko, O.D.; Ilyin, S.A. (Інститут програмних систем НАН України, 2024)
The work developed and considered a software system aimed at creating a virtual file system (VFS) based on FUSE, which provides a convenient and flexible interface for interacting with the file structure. The main goal of this project is to speed up file processing by customizing file system operations and creating a tool that allows users to easily manipulate the virtual file structure using a console interface. The development is intended for data processing and storage on operating systems of the Unix family. The functional tasks of the software system are focused on creating a virtual file system (VFS) based on FUSE with the aim of providing users with a convenient interface for interacting with the file structure. The main goal is to provide functionality for creating and deleting objects, obtaining detailed information about file attributes, reading and writing file contents, working with symbolic links, and navigating and interacting with directories. This includes the ability to create new files and directories, delete objects, get detailed information about file attributes, read and edit their contents, and work with symbolic links. The further goal is to create a convenient and functional tool for users, which can be used for conducting experiments, training or solving specific tasks, while providing flexibility and efficiency of interaction with the FUSE-based file system through the console interface.Prombles in programming 2024; 2-3: 334-342